PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA MATERI KOSAKATA KELAS IV SD NEGERI NAPUNGLANGIR - Paula Emerentiana; Veronika Jeo; Lukas Bera (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The issue addressed in this study is that students' vocabulary mastery remains low; they struggle to comprehend word meanings, synonyms, antonyms, and word usage within sentences. Furthermore, instruction has not sufficiently incorporated activities that actively involve students, thereby limiting opportunities for interaction, discussion, and the identification of word pairs—factors that ultimately impact student learning outcomes. This study aimed to determine the effect of the "Make A Match" cooperative learning model on student learning outcomes in the Indonesian language subject, specifically in the vocabulary unit, for fourth-grade students at Napunglangir Public Elementary School. This study was a quantitative, pre-experimental study using a one-group pretest-posttest design. The sample consisted of 18 fourth-grade students at Napunglangir Public Elementary School. The data collection techniques relied on tests and observations. The research instruments consisted of test items and observation sheets. The data analysis techniques employed a normality test and a hypothesis test. The results showed that the percentage of students achieving mastery increased from 0% on the pretest to 77.78% on the posttest. The results of the normality test using the Shapiro-Wilk test showed a significance value of 0.06 for the pretest and 0.07 for the posttest. Since both significance values were greater than 0.05, the data were deemed to be normally distributed and thus met the requirements for a Paired Sample t-test. The results of the Paired-Sample t-test showed a significance value (Sig., 2-tailed) of 0.000 (<0.05), indicating that the implementation of the "Make A Match" learning model had a significant effect on student learning outcomes in the Indonesian language subject, specifically the vocabulary unit, for fourth-grade students at Napunglangir Public Elementary School.